2021
DOI: 10.1039/d1cp03215a
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of closo-dodecaborates M2B12H12 (M = Li, Na, K) as solid-state electrolyte materials

Abstract: The closo-dodecaborates M2B12H12 (M = Li, Na, K) are studied using first-principles DFT calculations, where this emerging category of BnHn materials is considered as a new class of candidate electrolytes for solid-state batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Thus, one can conclude that the high-temperature phase is statically disordered with a high activation energy of rotation and without dynamical disordering. Previous research that used the PBE functional and AIMD, where dynamic disorder and full rotation were seen, are less reliable because of the underestimation of the anion–anion interaction and lack of van der Waals corrections, which are important in this system.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, one can conclude that the high-temperature phase is statically disordered with a high activation energy of rotation and without dynamical disordering. Previous research that used the PBE functional and AIMD, where dynamic disorder and full rotation were seen, are less reliable because of the underestimation of the anion–anion interaction and lack of van der Waals corrections, which are important in this system.…”
Section: Resultsmentioning
confidence: 81%
“…Classical molecular dynamics (MD) also supported this and revealed that asymmetric anions like CB 11 H 12 enhance vacancy formation and increase ionic conductivity. , However, AIMD calculations are constrained by the short timescale and small system sizes, which often limits realism in the description of phase transitions. Also, such AIMD or other DFT calculations were performed using the PBE functional without any van der Waals corrections, ,, even though it was proven that van der Waals interactions cannot be neglected in these systems . Moreover, in Li 2 B 12 H 12 , within the PBE functional, the lowest energy phase differs from the experiment .…”
Section: Introductionmentioning
confidence: 99%
“…(D) Fully relaxed crystal structure of M 2 B 12 H 12 (M = Li, Na, K), (E) Calculated heat capacity at constant pressure as a function of temperature; (F) Unit cell volume of the Li 2 B 12 H 12 , Na 2 B 12 H 12 , and K 2 B 12 H 12 . Reproduced with permission 146 . Copyright 2021, Royal Society of Chemistry.…”
Section: Advanced Thermal Simulation Techniques In Sslbmentioning
confidence: 99%
“…Heat capacity significantly affects the high temperature tolerance and determines thermal stability. Mounkachi et al 146 investigated the feasibility of closo‐dodecaborates M 2 B 12 H 12 (M = Li, Na, K) as SSEs (Figure 13D–F). The electronic, vibrational and thermodynamic properties of M 2 B 12 H 12 structures were calculated based on the first‐principles study.…”
Section: Advanced Thermal Simulation Techniques In Sslbmentioning
confidence: 99%
“…Borohydrides have recently caught increasing interest as promising candidates for SSEs. Compared with other SSE materials, borohydrides offer many benefits such as softness, lightness, thermal/chemical/reduction stability, and negligible grain boundary resistance. Many borohydride-based all-solid-state Li/Na batteries have been successfully designed and have partly exhibited excellent performances of high energy density or fast-charging capability. , Applied as K-ion SSEs, some borohydrides are also the ones with great potential. KCB 11 H 12 undergoes a order–disorder transformation at a lower temperature than the MCB 11 H 12 (M = Li, Na) analogues and achieves a K-ion conductivity of 3.2 × 10 –4 S cm –1 at about 88 °C in the disordered phase . Although this value is still lower than that of MCB 11 H 12 (M = Li and Na), it has placed KCB 11 H 12 among the leading K-ion SSEs.…”
Section: Introductionmentioning
confidence: 99%